PEMBERDAYAAN MASYARAKAT BERBASIS EKONOMI KERAKYATAN DENGAN PERAN CREDIT UNION - Epsilandri Septyarini; Bernadetta Diansepti Maharani (MANAJEMEN DEWANTARA, 2019)
In order to create an independent state of society and to be able to realize the potential capabilities which are possessed, then it is highly required the activities within the framework of community empowerment. The empowerment is expected to be able to change the life order of the community towards a better way, as the nation's aim to form a society which are fair, democratic, prosperous and advanced. The state has important duties and responsibilities for the welfare of its people. However, meeting community needs and social problems is not easy to be solved in one time with the existing development program. Indonesia is too wide and has a population that is too large to be reached out at one time by the rush of development. Seeing this phenomenon, it needs a real alternative solutions in supporting the welfare of society through community-based empowerment programs.This is a research that combines qualitative and quantitative approaches with concurrent triangulation models. The sample in this study was Mitra Parahita Credit Union in Gunung Kidul. The subjects of this study are 100 active members of Credit Union, and Credit Union Mitra Parahita manager. The purpose of this study is to evaluate the extent of the presence of Credit Union in empowering members and the community and also to find out how Credit Union is addressing the needs and problems of the members with the carried out empowerment. The research data are analyzed by clarifying the data based on the variety of available data, then linking it with all data and information obtained from literature, documents, surveys, in-depth interviews and field observations.The result of analysis shows that Credit Union also plays a role in empowering the community socially and economically. The empowerment program conducted by the Credit Union helps members become more progressive, independent and prosperous in accordance with the principles of people's economy. Empowerment carried out by the Credit Union is also felt to be able to increase the value and dignity of members and to make each member as well play an active role in caring for the weak.Keywords : Credit Union, Democratic Economy, Community Empowerment